MEKANISMA RESONANT TUNNELING DALAM DIODA 5-DOPED SINGLE BARRIER DENGAN SIMULASI NUMERIK - Mulyanti, Budi
To analyze the resonant tunneling mechanism of the S-doped single barrier resonant tunneling diodes, the transmission spectra and I-V characteristics for the conduction band electrons are calculated. Numerical methods are used to solve Schroedinger and Poisson Equations simultaneously to calculate energy band diagrams for different the width of barrier, 'external bias condition, peak doping concentration, band offset, and FWHM (Full-width at half maximum). Numerical simulations are also used to calculate the corresponding transmission spectra under various bias conditions. The calculated I-V characteristics for different peak doping concentration are presented. The influence of the FWHM on the I-V characteristics is also examined